2013
DOI: 10.1016/j.ctim.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of yoga and mindfulness as complementary therapies for addiction

Abstract: Summary This paper reviews the philosophical origins, current scientific evidence, and clinical promise of yoga and mindfulness as complementary therapies for addiction. Historically, there are eight elements of yoga that, together, comprise ethical principles & practices for living a meaningful, purposeful, moral and self-disciplined life. Traditional yoga practices, including postures and meditation, direct attention towards one’s health, while acknowledging the spiritual aspects of one’s nature. Mindfulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(101 citation statements)
references
References 53 publications
3
93
0
5
Order By: Relevance
“…The Hindu philosophy of yoga, originating during the second century B.C, is based on eight limbs of Ashtang yoga: 1) compromised of ethical disciplines, 2) individual observances, 3) posture, 4) breath control, 5) withdrawal of senses, 6) concentration, 7) meditation, and 8) enlightenment [1]. In western societies, the term yoga is now a general term that describes a practice which focuses on breathing techniques, postures, strengthening exercises, and meditation [2].…”
Section: Introductionmentioning
confidence: 99%
“…The Hindu philosophy of yoga, originating during the second century B.C, is based on eight limbs of Ashtang yoga: 1) compromised of ethical disciplines, 2) individual observances, 3) posture, 4) breath control, 5) withdrawal of senses, 6) concentration, 7) meditation, and 8) enlightenment [1]. In western societies, the term yoga is now a general term that describes a practice which focuses on breathing techniques, postures, strengthening exercises, and meditation [2].…”
Section: Introductionmentioning
confidence: 99%
“…35 Khanna S, in a narrative review suggested that the skills, insights, and self-awareness learned through yoga and mindfulness practice can target multiple psychological, neural, physiological, and behavioral processes implicated in addiction and relapse. 34 As described by Bernstein, yoga and meditation may also act by targeting the comorbid conditions of obesity and assist with weight loss or maintenance in the following ways: 28  Increasing energy expenditure during yoga sessions;  Allowing for additional exercise outside yoga sessions by reducing back and joint pain; 343  Heightening mindfulness, improving mood, and reducing stress, which may help reduce food intake;  Allowing individuals to feel more connected to their bodies, leading to enhanced awareness of satiety and the discomfort of overeating;  Decreasing emotional eating (eating in response to negative emotions such as boredom, stress, or sadness) and external eating (eating in response to food-related stimuli such as the taste, sight, or smell of palatable foods;  Achieving relaxation that helps to cope with stressful situations which cause addictive behaviors, like comfort food overconsumption and alcohol intake.…”
Section: (Figure 4)mentioning
confidence: 99%
“…33 Yoga and meditation can target multiple brain regions, and change the functional connections between them, that lead to addictive behaviors. 34 It also acts by increased present moment and self awareness, greater self regulation and reduced reactivity to substance cues. 35 Khanna S, in a narrative review suggested that the skills, insights, and self-awareness learned through yoga and mindfulness practice can target multiple psychological, neural, physiological, and behavioral processes implicated in addiction and relapse.…”
Section: (Figure 4)mentioning
confidence: 99%
“…Exercise and yoga may reduce levels of stress and anxiety that lead people to misuse prescription and OTC drugs [30,31]. Extracurricular classes (e.g.…”
Section: Prescription and Over-the Counter Drug Use In The United Stamentioning
confidence: 99%